Grayanotoxin (Mad Honey) - Ongoing Consumption After Poisoning - DENİZBAŞI ALTINOK, ARZU; AKOĞLU, HALDUN; ONUR, ÖZGE ECMEL (AVES YAYINCILIK, 2013)
Background: Some honey types in certain geographical regions may cause toxic effects on people. This type of honey is known as mad honey in Turkey. The toxic ingredient of this honey is called Grayanotoxin I. The consumption of mad honey can cause severe bradycardia, hypotension, dizziness, nausea and vomiting. Aims: Our study is aimed at analysing patients diagnosed with mad honey poisoning and their behaviour towards the consumption of this honey after diagnosis. Study Design: Cross sectional study. Methods: This cross-sectional study was based on complaints and findings of mad honey poisoning. Patient information and findings at the time of admission were compared with those at one month after discharge through telephone interviews. They were asked if either they or their relatives had continued consuming the same honey. Frequency data such as gender, purpose of honey consumption, first complaints and continuance of honey consumption are shown as number (n) and percentage (%). A Chi Square test was conducted to determine the difference between groups. Results: 38 patients were participated in this study; 18 of the patients had to be followed up in a coronary intensive care unit. We were able to reach 34 patients by phone after discharge. It was found that 12 of 16 patients discharged after emergency unit observation or their close relatives were continuing to consume mad honey, whereas 16 (88.9%) of the 18 patients under coronary intensive care had discontinued consuming mad honey. The difference in the continuation of mad honey consumption between patient groups followed-up in the intensive care unit and those discharged after emergency observation was statistically significant. Conclusion: Hazards associated with and serious consequences following the consumption of mad honey must be clearly explained to patients who are found to be consuming mad honey.
Keywords: Honey; poisoning; grayanotoxin I; TURKEY